Understanding Online Consumer’s Inter-Purchase Time - KIM, Youngsoo (Institutional Knowledge at Singapore Management University, 2013)
This study is motivated by the premise that online consumers can make a purchase at any time of day if they have even a tiny time slot along with Internet access. Given the increased shopping time flexibility, we first examine the patterns of online purchase timing at an online shopping mall handling diverse products (e.g., Amazon.com). The results show (1) the breakdown of purchase timing regularity and (2) the change of weekly spike purchase occurrence. Second, we build online inter-purchase time and price promotion utilization models and estimate them with the data collected from one of the premier online shopping malls in Korea. We find that online shopping malls need to start marketing activities immediately after a transaction because as inter-purchase time increase the likelihood of another transaction substantially drops. We also find three effects of a price promotion: (1) a price promotion can directly induce consumers to purchase any items sooner than necessary, (2) consumers who take advantage of a price promotion at the current transaction are likely to accelerate next purchase time (indirect effects of price promotion), and (3) online consumers experiencing a price promotion are more likely to take advantage of another price promotion. Our model also gives insight on consumers’ adaptation process to online commerce (e.g., the increase of the utilization of a price promotion with online shopping experience). Our results provide some useful bases for differentiation of marketing strategy based on customer segmentation by recency (time since last purchase), purchase frequency and recent cumulative expenditure.